A Novel Method for Ultrasonic Evaluation of Horizontal Defects Using Time-of-Flight Diffraction - Parastoo Bagheri (Iranian Journal of Oil & Gas Science and Technology, 2014)
Time-of-flight diffraction method (ToFD) is an amplitude-independent sizing method which is based on the measurement of time-of-flight of defect tip diffracted waves. Although ToFD can measure through-wall length of defect accurately, this method is not capable of measuring horizontal defect size. In this paper, a new ToFD method for evaluating horizontal planar defects is presented. The finite element method (FEM), using the ABAQUS software package, is employed to simulate the ultrasonic wave behavior in the test blocks and its interaction with the embedded planar defects. The phased array technology is also used to model the ultrasonic inspection system parameters. FEM simulation of the new ToFD method for different crack sizes shows that, compared to the conventional ToFD method, the accuracy of results is within acceptable range to use the novel technique for measuring the horizontal planar defects.